What Can Queer Theory Do for Intersex? - Morland, Iain (GLQ: A Journal of Lesbian and Gay Studies, 2009)
In this essay I explore how queer theory might account for postsurgical intersex bodies of diminished genital tactility. In other words, I evaluate whether a critique of surgery’s effects is possible from a queer theoretical perspective on the body. I contend that for this purpose queer theory must do more than focus on bodily sensations such as pleasure, shame, and touching. The essay makes four key claims: first, that the desensitized postsurgical body cannot be accounted for by a queer discourse in which sexual pleasure is a form of hedonistic activism; second, that a queer discourse of shame enables a degree of critical engagement with the surgical creation of atypically sensate bodies; third, that pleasure and shame are both queer sensations, and queer theory’s assumption of a sensorial basis to cultural critique, which is exemplified by the queer touch, flounders when confronted with the desensitized intersex body; fourth, that if queer theory is figured as a kind of reaching—but not necessarily touching—then it can be of greater use in accounting for the problematic yet ambivalent effects of intersex surgery.
Keywords: LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; premier cycle; queer; ressource en ligne; thématiques; études culturelles; études littéraires

Le personnage intersexué: Voie de renouvellement de l'imaginaire des sexes/genres? - Boisclair I. (Nouvelles Questions Feministes, 2008)
Cet article se penche sur le personnage intersexué dans trois œuvres littéraires contemporaines (La tête en bas, de Noëlle Châtelet [Paris : Seuil, 2002]; Middlesex, de Jeffrey Eugenides [Paris : L'Olivier, 2003]; et Le saut de l'ange, de Maud Marin [Paris: Fixot, 1987]). On s'intéresse à ce que ces œuvres « disent » sur l'intersexualité, depuis une perspective sociosémiotique englobant, de façon synthétique, aussi bien le paratexte, l'écriture, que le réel représenté. Si deux de ces textes présentent l'intersexualité comme une condition honteuse ou malheureuse, un autre la dédramatise, la posant comme un possible identitaire parmi d'autres dans la multitude.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; identités LGBTQIA2+; lit4700; personnes intersexes; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociologie; sémiotique; thématiques; études littéraires

All these poses, such beautiful poses: Articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright's direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an "utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo." Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright's musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the "Clone." In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; approches et analyses; arts; culture populaire; discipline; discours dominant; ethnographie; genre; hétérosexisme; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; systèmes d'oppressions

Narrations déviantes : l'intimité entre femmes dans l'imaginaire français du dix-septième siècle - Legault, Marianne (Presses de l'Université Laval, 2008)
Si les rapports intimes entre les femmes ont toujours existé, comment expliquer leur absence dans le discours critique littéraire français malgré la foulée des études récentes sur les femmes, des études gays et lesbiennes et des études queers ? Voulant remédier à cette absence, ce livre retrace une généalogie de l’intimité féminine dans la littérature française du dix-septième siècle. Suivant une lecture qui s’inspire des études lesbiennes et queers, il explore l’effet d’un héritage androcentré sur l’intimité féminine au Grand Siècle, telle qu’elle a été envisagée par l’imaginaire d’Honoré d’Urfé dans L’Astrée et d’Isaac de Benserade dans Iphis et Iante. L’anxiété masculine qui se dégage de leurs représentations contraste avec la célébration de l’intimité féminine chez Madeleine de Scudéry dans Mathilde (d’Aguilar) et chez Charlotte-Rose de Caumont de La Force dans Plus belle que fée, deux œuvres qui élargissent les possibilités érotiques au sein des rapports intimes entre femmes au-delà de ce que les écrivaines avaient auparavant osé.
Keywords: 1600-1699; approches et analyses; arts; discipline; discours dominant; europe; france; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; queer; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

Épistémologie du placard - Sedgwick, Kosofsky Eve (Éditions Amsterdam, 2008)
Lorsqu’il fut publié pour la première fois aux États-Unis en 1990, Épistémologie du placard devint immédiatement un classique qui, aux côtés des travaux de Judith Butler et de Teresa de Lauretis, posa les termes de la « théorie queer ». À mi-chemin entre les études féministes et les gay and lesbian studies, Eve Kosofsky Sedgwick déconstruit la sexualité comme Butler le genre. Dans cet ouvrage de référence, elle affirme que l’ensemble de la culture occidentale moderne s’articule autour de l’opposition homo/hétérosexuel et que celle-ci affecte les binarismes qui structurent l’épistémologie contemporaine, de savoir/ignorance à privé/public en passant par santé/maladie.S’appuyant sur de nombreux textes datant de la fin du XIXe et du début du XXe siècles (Wilde, Proust, Nietzsche, Melville et James), l’auteur traque l’émergence des nouveaux discours institutionnels médicaux, juridiques, littéraires et psychologiques, qui produiront en miroir les figures de « l’homosexuel » et de « l’hétérosexuel », au détriment des multiples différences au cœur des sexualités.
Keywords: amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; lit4700; premier cycle; queer; régions géographiques; sciences humaines; sexualité; soc2014; thématiques; épistémologie; états-unis; études littéraires

Les conceptions de l’identité sexuelle, le postmodernisme et les textes littéraires - Boisclair, Isabelle; Saint-Martin, Lori (Recherches féministes, 2006)
Le présent article trace d’abord un bref portrait de trois conceptions dominantes de l’identité sexuelle : le modèle patriarcal, le modèle féministe et le modèle postmoderne. Puis, après avoir présenté plus longuement le dernier, il analyse deux romans relayant cette conception postmoderne de l’identité de sexe/genre, l’un écrit par un homme (Self, de Yann Martel, paru en 1996), et l’autre par une femme (Ce qu’il en reste, de Julie Hivon, paru en 1999). Dans ces deux romans, qui revêtent de ce fait une importante dimension politique, les identités figées sont mises à mal tant discursivement que formellement - par la déconstruction des signes du passé et la mise en place de dispositifs énonciatifs confondant hommes et femmes, par exemple. Ils participent ainsi à une conception culturaliste de l’identité sexuelle, selon laquelle le genre est une performance.,This article begins by briefly introducing three major frameworks for conceptualizing gender identity : a patriarchal model, a feminist model and a postmodern model. After exploring the third in greater depth, it offers a reading of two novels of postmodern gender identity, one by a male author (Self by Yann Martel, 1996), one by a female author (Ce qu’il en reste by Julie Hivon, 1999). Both novels, which are therefore strongly political, challenge the concept of predetermined gender identity on the levels both of discourse and of form, by deconstructing older concepts and by blurring gender lines. They are therefore grounded in a view of gender identity as cultural construction and performance.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (Cultural front, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

A bakhtinian perspective on feminist lesbian crime writing - Posman, Sarah (CLCWeb: Comparative Literature and Culture, 2006)
In her paper, "A Bakhtinian Perspective on Feminist Lesbian Crime Writing," Sarah Posman discusses how the Bakhtinian concepts "ethos" and "chronotope" add to the discussion of feminist lesbian crime writing. She sets out from a Bakhtinian typology of action stories and situates recent crime writing as a curious mixture of mission stories and transformation stories. Focusing on the innovative potential of feminist lesbian crime writing, Posman explores how such stories tackle the iconically masculine and heterosexual conventions of the detective story and manage to balance tradition and subversion successfully. Posman infuses her analysis with issues central to feminism and queer theory and considers how a feminist lesbian detective hero can "change the world," that is, how such an "other" ethos impinges on crime writing's conventional chronotopical constellation. The hero and world under discussion are those of the popular Kate Delafield series by Katherine V. Forrest.
Keywords: approches et analyses; arts; discipline; lesbianisme; personnes lesbiennes; queer; ressource en ligne; études littéraires

Deviant classics: Pulps and the making of lesbian print culture - Foote, Stephanie (Signs, 2005)
Keywords: approches et analyses; arts; cours; discipline; fem1300; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; thématiques; études littéraires

La pornographie comme espace de décentrement du discours hétéronormatif : l'exemple du roman Baise-moi de Virginie Despentes - Ouellette, Julie (Université du Québec à Montréal, 2005)
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; approches et analyses; arts; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; mémoires/thèses; périodes historiques; queer; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Touching feeling: Affect, pedagogy, performativity - Sedgwick, Eve Kosofsky (Duke University Press Books, 2003)
A pioneer in queer theory and literary studies, Eve Kosofsky Sedgwick brings together for the first time in Touching Feeling her most powerful explorations of emotion and expression. In essays that show how her groundbreaking work in queer theory has developed into a deep interest in affect, Sedgwick offers what she calls "tools and techniques for nondualistic thought," in the process touching and transforming such theoretical discourses as psychoanalysis, speech-act theory, Western Buddhism, and the Foucauldian "hermeneutics of suspicion." In prose sometimes somber, often high-spirited, and always accessible and moving, Touching Feeling interrogates—through virtuoso readings of works by Henry James, J. L. Austin, Judith Butler, the psychologist Silvan Tomkins and others—emotion in many forms. What links the work of teaching to the experience of illness? How can shame become an engine for queer politics, performance, and pleasure? Is sexuality more like an affect or a drive? Is paranoia the only realistic epistemology for modern intellectuals? Ultimately, Sedgwick's unfashionable commitment to the truth of happiness propels a book as open-hearted as it is intellectually daring.
Keywords: approches et analyses; arts; autobiographie; discipline; queer; émotions; études littéraires

Lectures du genre - Boisclair, Isabelle (Les éditions du remue-ménage, 2002)
Qu’en est-il du masculin et du féminin dans la production littéraire contemporaine? Que permettent d’apprendre sur les textes du passé les hypothèses actuelles quant au caractère culturel du dispositif de la différence des sexes? Autant de questions qui peuvent être soulevées au moment d’interroger les textes, en recourant aux notions de détermination et d’indétermination, de brouillage et de glissement du genre, qui sont reliées de près à celle de l’identité sexuelle. Chaque texte littéraire recèle une vision du genre sexuel et constitue à ce titre un lieu de médiation où il est possible de reproduire ce dispositif ou de le subvertir. Aborder la question du genre vient ouvrir, en quelque sorte, celle du féminin et poser, à ses côtés, celle du masculin, et, plus globalement, celle de la division du monde.
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; lit3495; premier cycle; queer; thématiques; écriture des femmes*; études littéraires

Femme/Butch family romances - Harris, Laura A. (Journal of Lesbian Studies, 2002)
My essay theorizes femme/butch family romances against the grain of dominant feminist and lesbian thought that desexualizes the space of mother/daughter desire. I do so through a reading/recoding of the infringing incestuous mommie-boy desires that surface in an archetypal lesbian novel, Jane Rule's Desert of the Heart.
Keywords: approches et analyses; arts; butch; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; systèmes d'oppressions; études littéraires

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires

Narrative in the feminine Daphne Marlatt and Nicole Brossard - Knutson, Susan Lynne (Wilfrid Laurier University Press, 2000)
Que signifie raconter une histoire du point de vue d’une femme ? Comment les écrivain.e.s canadien.n.e.s anglophones et francophones ont-iels mis en pratique la théorie littéraire féministe ? Les écrivaines d'avant-garde Daphné Marlatt et Nicole Brossard répondent à ces questions, et à bien d'autres, dans leurs deux ouvrages révolutionnaires, désormais rendus plus accessibles grâce aux lectures narratologiques minutieuses et au contexte théorique de Narrative in the Feminine . Susan Knutson commence son étude par une analyse des contributions de Marlatt et Brossard à la théorie féministe internationale. La deuxième partie présente une lecture narratologique de How Hug a Stone , affirmant qu'au niveau le plus profond du récit, Marlatt construit un sujet humain inclusif en termes de genre qui par défaut ne se réfère pas au masculin générique mais au féminin. La troisième partie propose une lecture parallèle de Picture Theory , le roman ludique de Brossard qui nous entraîne dans des (re)lectures de nombreux autres textes écrits par Brossard, Barnes, Wittig, Joyce, de Beauvoir, Homer... pour ne citer qu'eux. Le chapitre 12 se termine par une réflexion sur l'expression <'e>criture au f<'e>minin — une contribution québécoise à un débat théorique international. Les lecteurices qui s’intéressent à l’écriture féministe et à la théorie du langage, ainsi que les étudiant.e.s et enseignant.e.s de littérature canadienne et d’études critiques et queer, trouveront ce livre inestimable pour ses lectures attentives, son aperçu scientifique et son extension du concept féministe du générique. Enfin, l'étude constitue un guide de deux ouvrages importants des principales écrivaines expérimentales du Canada et du Québec, Daphné Marlatt et Nicole Brossard.
Keywords: amériques; approches et analyses; arts; canada; discipline; littérature; queer; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires